2021
DOI: 10.3390/cells10010122
|View full text |Cite
|
Sign up to set email alerts
|

MG53, A Tissue Repair Protein with Broad Applications in Regenerative Medicine

Abstract: Under natural conditions, injured cells can be repaired rapidly through inherent biological processes. However, in the case of diabetes, cardiovascular disease, muscular dystrophy, and other degenerative conditions, the natural repair process is impaired. Repair of injury to the cell membrane is an important aspect of physiology. Inadequate membrane repair function is implicated in the pathophysiology of many human disorders. Recent studies show that Mitsugumin 53 (MG53), a TRIM family protein, plays a key rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 79 publications
0
35
0
Order By: Relevance
“…MG53, as a muscle-derived protein that circulates in the bloodstream, is known to facilitate repair of injury to multiple vital organs [81,82]. The tumor suppressor function of MG53 has just started to be appreciated.…”
Section: Discussionmentioning
confidence: 99%
“…MG53, as a muscle-derived protein that circulates in the bloodstream, is known to facilitate repair of injury to multiple vital organs [81,82]. The tumor suppressor function of MG53 has just started to be appreciated.…”
Section: Discussionmentioning
confidence: 99%
“…MG53 protein can be released from skeletal muscle as a myokine [44]. In mdx mice, a model of Duchenne muscular dystrophy, we previously demonstrated that increased serum MG53 level correlated with an increased serum CK level [29], indicating that elevated serum MG53 level serves as a biomarker for muscle membrane damage.…”
Section: Mg53 Is Implicated In the Membrane Fragility Of G93a Diaphragm Fast-and Slow-type Musclesmentioning
confidence: 94%
“…At the membrane, TRIM72 protein binds to phosphatidyl serine to mediate the recruitment of vesicles at the injured site [104]. Interestingly, TRIM72 can be secreted and circulate throughout the entire body to reach all tissues and organs, allowing the recombinant TRIM72 protein to have therapeutic benefit in treatment of injuries to multiple tissues, such as the heart, kidney, lung, brain, liver, skin, skeletal muscle, and cornea [105]. Ablation of the TRIM72 gene leads to increased susceptibility to ischemia-reperfusion and overventilation-induced ALI in mice [97].…”
Section: Trim65mentioning
confidence: 99%